Molecular Identification of Three Potyviruses Infecting Allium cepa var. aggregatum and Allium sativum in Central Cultivation Areas of Indonesia - Adyatma Irawan Santosa; Muh Amat Nasir; Ali Çelik; Tahir Farooq; Aprilia Sufi Subiastuti (Caraka Tani: Journal of Sustainable Agriculture, 2024)
One hundred and twenty shallot (Allium cepa var. aggregatum) and 22 garlic (Allium sativum) samples were collected from major growing regions and markets to determine the distribution and molecular diversity of 3 potyviruses: leek yellow stripe virus (LYSV), onion yellow dwarf virus (OYDV), and shallot yellow stripe virus (SYSV) in Indonesia. The results of reverse transcription-polymerase chain reaction (RT-PCR) showed that 83% of shallot and all garlic samples were infected by at least 1 virus species. Coat protein (CP) region of 8 Indonesian LYSV, 19 OYDV, and 10 SYSV isolates were sequenced and given accession nos. OR772038-OR772082 in NCBI GenBank. Five isolates were recombinants according to analysis using the Recombination Detection Program (RDP v5.30). The phylogenetic tree deduced that 6 LYSV Indonesian and 2 China imported isolates belong to S-type. All tested OYDV isolates, including the 19 isolates, were clustered separately according to their respective hosts: onion and garlic. The 10 Indonesian SYSV isolates were clustered together in the same group and thus shown to be closely related. All isolates tested in this study were estimated to be still within their respective species demarcation according to percentage identity analysis. This was the most comprehensive molecular study on LYSV, OYDV, and SYSV that may help to find sustainable management strategies according to conditions in Indonesia and contribute to the global knowledge on the genetic diversity of the 3 viruses.